PS 16-13 ON THE ORIGIN OF BRAIN RENIN. (September 2016) - Van Thiel, Bibi; Te Riet, Luuk; Garrelds, Ingrid; Uijl, Estrellita; Severs, David; Qadri, Fatimunnisa; Natalia, Alenina; Bader, Michael; Danser, Alexander
Abstract: Objective: A renin-angiotensin system (RAS) in the brain is believed to contribute to blood pressure regulation. Given the presence of the blood-brain barrier, brain RAS activity most likely depends on synthesis of (pro)renin in the brain. In support of this concept, an intracellular, non-secreted form of renin has been described in the brain, depending on an alternative transcript of the renin gene. In the present study, we set out to quantify brain (pro)renin, both before and after buffer perfusion of the brain, in normal mice, renin knockout (KO) mice, DOCA-salt-treated mice (which have been reported to display brain RAS activation), and angiotensin II-infused mice. Design and method: Brain nuclei were homogenized and incubated with angiotensinogen to detect AGA, both before and after acid activation of prorenin, with or without the renin inhibitor aliskiren to correct for non-renin-mediated AGA. Results: Renin-dependent (i.e., aliskiren-inhibitable) AGA was readily detectable in brain nuclei, the highest AGA being present in brainstem (>thalamus = cerebellum = striatum = midbrain > hippocampus = cortex). Brain AGA increased non-significantly after prorenin activation, suggesting that brain prorenin levels are low or absent. Buffer perfusion reduced AGA in all brain areas by > 60%. Plasma renin (expressed per mL plasma) was 40–800x higher than brain renin (expressed per g tissue). Plasma prorenin levels were lower than plasma renin levels. AGA was undetectable in plasma and brain of renin KO mice. DOCA-salt and angiotensin II suppressed plasma renin, and parallel decreases were observed for brain renin. Conclusions: Brain renin levels (per g tissue) correspond with the amount of renin present in 1–20 microliter blood plasma. Brain renin disappears after buffer perfusion, and varies in association with plasma renin. This indicates that renin detected in brain nuclei represents plasma renin and/or locally activated plasma prorenin. DOCA-salt exposure does not selectively increase brain renin expression.